Differential circulating miRNA profiles identified miR-423-5p, miR-93-5p, and miR-4532 as potential biomarkers for cholangiocarcinoma diagnosis - Kittiya Supradit; Sattrachai Prasopdee; Teva Phanaksri; Sithichoke Tangphatsornruang; Montinee Pholhelm; Siraphatsorn Yusuk; Kritiya Butthongkomvong; Kanokpan Wongprasert; Jutharat Kulsantiwong; Amnat Chukan; Smarn Tesana; Veerachai Thitapakorn (PeerJ, 2024)
Background Cholangiocarcinoma (CCA) is high in morbidity and mortality rates which may be due to asymptomatic and effective diagnostic methods not available. Therefore, an effective diagnosis is urgently needed. Methods Investigation of plasma circulating miRNA (cir-miRNA) was divided into two phases, including the discovery phase (pooled 10 samples each from three pools in each group) and the validation phase (17, 16, and 35 subjects of healthy control (HC), O. viverrini (OV), and CCA groups, respectively). The plasma from healthy control subjects, O. viverrini infected subjects, and CCA subjects was used. In the discovery phase, plasma was pooled by adding an equal volume of plasma, and cir-miRNA was isolated and analyzed with the nCounter® SPRINT Profiler. The significantly different cir-miRNAs were selected for the validation phase. In the validation phase, cir-miRNA was isolated and analyzed using real time-quantitative polymerase chain reaction (RT-qPCR). Subsequently, statistical analysis was conducted, and diagnostic parameters were calculated. Results Differential plasma cir-miRNA profile showed at least three candidates including miR-423-5p, miR-93-5p, and miR-4532 as potential biomarkers. From validation of these cir-miRNAs by RT-qPCR, the result showed that the satisfied sensitivity and specificity to differential CCA group from HC and OV group was obtained from miR-4532 (P < 0.05) while miR-423-5p and miR-93-5p can be used for differential CCA from OV and HC group (P < 0.05) with high specificity but limited the sensitivity. In conclusion, candidate cir-miRNAs have been identified as potential biomarkers including miR-423-5p, miR-93-5p and miR-4532. Screening by miR-4532 and confirmed with miR-423-5p, miR-93-5p were suggested for differential CCA patients in the endemic area of O. viverrini.